Penggunaan Kitosan Sebagai Bahan Pengawet Pada Sirup Nanas (Ananas comosus (L.) Merr) - Effendi, Raswen; ', Nurazizah; ', Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The aim of this research was to know the effect of presented of several chitosan concentration on the pineapple syrup to quality and growth of mold during storage and to know the best concentration. This research had been using group randomized design (GSD), i. e: K1 (without presented of chitosan solution); K2 (presented 0,5% of chitosan solution); K3 (presented 1,0% of chitosan solution); K4 (presented 1,5% of chitosan solution); K5 (presented 2,0% of chitosan solution). Parameters  analyzed  were  dissolved  density  completely,  acidity  (pH),  viscosity, precipation, mold and organoleptic value included colour, taste, aroma,  viscosity degree and valuasion totality. The  result  showed  that  present  of  several  chitosan concentration had significant effect on the dissolved density completely, acidity (pH), viscosity and organoleptik value of pineapple syrup. By generally presented chitosan on the pineapple syrup had been advance dissolved density completely, viscosity and precipation, however pH had been down. Present chitosan had been growth of mold blocked on pineapple syrup. Be based on organoleptic test of pineapple syrup on general valuation could more acceptable by panelist until 1,0%.   Keyword: pineapple syrup, preservatives, chitosan